2020
DOI: 10.1097/j.jcrs.0000000000000341
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser–assisted cataract surgery in eyes with shallow anterior chamber depth: comparison with conventional phacoemulsification

Abstract: Purpose: To compare the postoperative outcomes between femtosecond laser–assisted cataract surgery (FLACS) and conventional phacoemulsification in eyes with shallow anterior chamber depth (ACD). Setting: Eye Clinic, NEUROFARBA Department, University of Florence, Italy. Design: Prospective case series. Methods: Forty eyes of 40 patients with senile cataract and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Although numerous studies have assessed FLACS outcomes and reported adverse events, the advantage of the MAUDE database is its inclusion of ophthalmologists from a wide range of backgrounds and practice settings. [1][2][3][4][5][6][7][8][11][12][13][14] The FDA MAUDE database represents the single largest publicly available repository of complications related to FLACS in the United States, reflecting this diversity of realworld surgeon experience with both conventional phacoemulsification and FLACS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous studies have assessed FLACS outcomes and reported adverse events, the advantage of the MAUDE database is its inclusion of ophthalmologists from a wide range of backgrounds and practice settings. [1][2][3][4][5][6][7][8][11][12][13][14] The FDA MAUDE database represents the single largest publicly available repository of complications related to FLACS in the United States, reflecting this diversity of realworld surgeon experience with both conventional phacoemulsification and FLACS.…”
Section: Discussionmentioning
confidence: 99%
“…5 Among the possible advantages of FLACS, it has been shown to reduce endothelial cell loss in eyes with shallow anterior chambers, Fuchs dystrophy, and dense cataracts. [6][7][8] In the present work, we report on the landscape of complications associated with FLACS that are reported in the FDA's Manufacturer and User Facility Device Experience (MAUDE) database and the number of complications reported per year over the past decade. As a repository for adverse event reports, the MAUDE database serves as one of the FDA's tools for postmarketing surveillance of medical devices.…”
mentioning
confidence: 99%
“… 8 A recent prospective study has shown that FLACS is safer in eyes with shallow anterior chambers of less than 2mm. 18 …”
Section: Corneal Recoverymentioning
confidence: 99%
“…Despite the scarcity of evidence regarding its efects on the ONH, the number of publications stating that FLACS is especially useful in certain conditions related to glaucoma keeps increasing [6,7]. Tese conditions include pseudoexfoliation, narrow anterior chamber, angle closure, nanophthalmos, and phacomorphic glaucoma [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%